Evaluation of Total Flavonoid, Total Phenolic Contents, and Antioxidant Activity of Strychnobiflavone - Sana Ullah; Chang-Gu Hyun (Indonesian Journal of Chemistry, 2020)
This work evaluates the antioxidant activity of strychnobiflavone due to the increasing demand of the antioxidant agents day by day. Various in vitro antioxidants assays such as 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) were used to investigate the antioxidant activity of strychnobiflavone. The results of both DPPH and ABTS show that strychnobiflavone increase the scavenging activity in a concentration-dependent manner due to the phenolic and flavonoid contents. This study revealed that strychnobiflavone is one of the promising and an effective compound for the antioxidant agent.